PURIFICATION AND CHARACTERIZATION OF BACTERIOCIN FROM Lactobacillus acidophilus HT1 AND ITS APPLICATION IN A CREAM FORMULA FOR THE TREATMENT OF SOME SKIN PATHOGES - & et al., Rasheed (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2020)
This study was aimed to purified and characterized  the  bacteriocin produced from Lactobacillus acidophilus HT1,  in order to use it in a skin pharmaceutical formula. The optimal conditions for bacteriocin production was investigated and results showed that modified nutrient broth was the best medium with glucose (30 gm/L) and yeast extract (7 gm/L) with peptone (7 gm/L) were the optimum carbon and nitrogen sources. In addition, 2% inoculum size, 37C◦ and pH 6.4 were the optimal conditions to obtain maximum bacteriocin of 640 AU/ml after 24 hrs. The bacteriocin was purified using 70% ammonium salt saturation and gel filtration with sephadex G50 that resulted 20 % yield and 2560 AU/ml of activity, then the partial purified bacteriocin was characterized and found  the bacteriocin was protein in nature and kept its activity after 10 min at 20, 30 and 40◦C, however 50% of the activity was lost at 50C◦. Moreover, it showed stability at pH 6 and 7 for 30 min whereas; no activity was observed at pH 4 and 9. In addition, results showed that bacteriocin has a bactericidal effect rather than bacteriostatic. A cream formula contained the bacteriocin was prepared which already examined in vitro and in vivo. The effectiveness of the formula was confirmed using Klebsiella sp., Staphylococcus aureus and Pseudomonas aeruginosa as indicator strains. Results established that treatment at the onset time was more effective and the time of healing was decreased.